2016
DOI: 10.1002/14651858.cd011255.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Skin grafting and tissue replacement for treating foot ulcers in people with diabetes

Abstract: Based on the studies included in this review, the overall therapeutic effect of skin grafts and tissue replacements used in conjunction with standard care shows an increase in the healing rate of foot ulcers and slightly fewer amputations in people with diabetes compared with standard care alone. However, the data available to us was insufficient for us to draw conclusions on the effectiveness of different types of skin grafts or tissue replacement therapies. In addition, evidence of long term effectiveness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 65 publications
1
45
0
Order By: Relevance
“…The value of ADM in increasing healing rates in both acute and chronic wounds has been reflected over numerous trials (24). Similar conclusions have been drawn from a recent systematic review in the context of DFUs (40). Despite the handful of RCTs completed, notable bias was observed due to the difficulty of assessor blinding in the presence of a dermal substitute.…”
Section: Fiberglass Castssupporting
confidence: 80%
See 1 more Smart Citation
“…The value of ADM in increasing healing rates in both acute and chronic wounds has been reflected over numerous trials (24). Similar conclusions have been drawn from a recent systematic review in the context of DFUs (40). Despite the handful of RCTs completed, notable bias was observed due to the difficulty of assessor blinding in the presence of a dermal substitute.…”
Section: Fiberglass Castssupporting
confidence: 80%
“…The aforementioned systematic review was published in the Cochrane Library in 2016 (40). Its aim was to determine the therapeutic benefits of skin grafting and tissue replacement therapy over the routine standard of care in patients with DFUs.…”
Section: Fiberglass Castsmentioning
confidence: 99%
“…Diabetic ulcer is a complex clinical problem requiring a multifaceted treatment plan with standard therapeutic components, including debridement of necrotic tissue, offloading, infection control, surgical revascularization, and limb elevation/compression (Ayello, 2005; Alexiadou and Doupis, 2012; Andrews et al, 2015). Skin grafts, including bioengineered or artificial skin, autografts, allografts, or xenografts from animal tissue, have produced promising results in clinical trials for diabetic foot ulceration (Santema et al, 2016). While many bioactive approaches have been explored to improve wound care in diabetic patients (Calderini et al, 2014), many of these have been found to be ineffective in clinical trials, and these non-healing wounds remain a major clinical challenge (Steed et al, 1992; Richard et al, 1995; Wieman et al, 1998; Steed, 2006; Uchi et al, 2009; Marti-Carvajal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After performing a TMA, wound closure is a pivotal element that must be tailored according to the wound's and the patient's conditions, and when appropriate, adjuvant local treatments must be considered (skin grafting, NPWT, application of PG) in order to speed up and maintain wound healing (58)(59)(60)(66)(67)(68)71).…”
Section: Discussionmentioning
confidence: 99%
“…Local flaps, characterised by skin without the presence of local necrosis and infection, and the transposition of neighbouring vascularised soft tissue allow coverage of a large defect (34,57). The split-thickness skin graft may be used with meshing that allows coverage of a larger area and decreases complications, such as a seroma or haematoma (58)(59)(60). Sometimes, delayed primary closure is a valid option (61); diabetic post-amputation wounds, in fact, tend to heal often by second intention, and the main disadvantage is the high complication rates in wound healing that range from approximately 40% to 70% (38,43,62,63).…”
Section: Postoperative Management Of Tmamentioning
confidence: 99%